The Future of Leadership: Developing the Next Generation of Leaders - Nasution, Ucok Binanga (Penelitian dan Pengembangan Ilmu, 2024)
This research investigates leadership development strategies for the younger generation in the digital era through a systematic literature review approach. The research background underlines the importance of a deep understanding of the concept of leadership, the influence of the digital era on the younger generation, and leadership development strategies that are appropriate to the digital context. The aim of the research is to explore various effective strategies in developing leadership in the next generation in the digital era. The research method involves the collection, selection, and analysis of relevant articles from reputable international databases. The results of the discussion highlight the importance of technology integration, structured mentoring and coaching, as well as developing soft skills with technology as the main strategies in developing leadership in the younger generation in the digital era. The implication of this research is the importance of adopting innovative and adaptive strategies in preparing future generations to become effective leaders in facing future challenges.